Elevated Pulse Pressure in Anesthetized Subjects Before Cardiopulmonary Bypass Is Associated Strongly With Postoperative Acute Kidney Injury Stage - Mitrev, Ludmil; Speich, Kelly G.; Ng, Spencer; Shapiro, Albina; Ben-Jacob, Talia; Khan, Majid; Nagubandi, Vineeth; Gaughan, John (Journal of cardiothoracic and vascular anesthesia, 2019)
To investigate whether pulse pressure (PP) in anesthetized patients undergoing cardiac surgery before and after cardiopulmonary bypass (CPB) is associated with higher postoperative acute kidney injury (AKI) stage. Retrospective cohort of 597 patients undergoing cardiac surgery. Single academic health care center. Adult patients undergoing cardiac surgery requiring CPB (coronary artery bypass grafting, valve, aortic, or combined surgery). Pulse pressure was assessed during 3 time periods: pre- and post-CPB, and in the first postoperative hour in the intensive care unit. Pulse pressure, patient characteristics, and intraoperative variables were evaluated using univariable generalized estimating equation analysis for a relationship with AKI stage. Significant risk factors from the univariable analysis then were evaluated in a multivariable generalized estimating equation analysis. Acute kidney injury stage was defined using the Acute Kidney Injury Network criteria. Stage of postoperative AKI. Intraoperative prebypass PP was associated independently and significantly with postoperative AKI stage (odds ratio 1.0107; 95% Confidence Interval, 1.0046-1.0168; p = 0.0005). For every 1-mmHg increase in PP, the odds of a higher AKI stage increased 1.07%. The 2 other periods were not found to be significant predictors of AKI stage. During general anesthesia prior to initiation of CPB, elevated PP is significantly predictive of postoperative AKI stage. This finding merits further research.